Isolation, identification and fermentation conditions optimization of high-yield amylase strains from tobacco and preparation of solid amylase preparations - SUN Zhikang, LI Xuanwen, JI Qiang, WU Na, ZHENG Chao, WU Han, YE Changwen, HUANG Kuo, HAO Jie (Zhongguo niangzao)
The high-yield amylase strains were screened from 20 strains of bacteria and 17 strains of fungi with amylase production ability isolated from the tobacco-growing soil. The screened strains were identified by morphological observation, physiological and biochemical tests and molecular biology techniques. The enzyme production conditions were optimized by single factor experiments, and solid amylase preparations were prepared through clarification, separation, and purification, and their stability was studied. The results showed that a high-yield amylase strain MK10163 was screened and identified as Bacillus amyloliquefaciens. The optimal fermentation conditions for amylase production were fermentation time 44 h, temperature 35 ℃, liquid loading volume 50 ml/500 ml, shaking speed 200 r/min, initial pH 6.0. Under these conditions, the amylase activity was (224.63±7.34) U/ml, which was 34.21% higher than that before optimization. The solid amylase preparation was obtained by clarifying with 1% calcium chloride and 1% disodium hydrogen phosphate and alcohol precipitation with 2 times volume of 95% ethanol. After freeze-drying, solid amylase preparation was obtained. The relative enzyme activity of solid amylase preparation was still 91.12% after storage for 60 d, indicating that it had strong stability.